The design of an efficient class E-LCCL capacitive power transfer system through frequency tuning method - Khairul Kamarudin Hasan; Shakir Saat; Yusmarnita Yusop; Huzaimah Husin; Nor Diyana Md Sin (International Journal of Electrical and Computer Engineering (IJECE), 2021)
In this work, the optimum zero voltage switching (ZVS) of Class E-LCCL capacitive power transfer (CPT) was determined via frequency tuning method. Through this an efficient system can be guanranteed although there is a change in the capacitive plates distance. This study used a Class-E LCCL inverter, as it can operate at a high alternate current frequency, besides producing low switching losses and minimal power losses. Specifically, this study conducted simulations and experiments to analyse the performance of an LCCL CPT System at 1 MHz operating frequency and 24 V DC supply voltage. Using an air gap distance of 0.1 cm, the designed CPT system prototype successfully achieved an output power of 10W and an efficiency of 95.45%. This study also found that by tuning the resonant frequency of the Class E-LCCL system, the optimum ZVS can be obtained although capacitive plate distance was varied from 1-3 cm via experimental. The results of this study could benefit medical implant and portable device development, consumer electronics, and environments that involve electrical hazards.